2012
DOI: 10.1111/j.1538-7836.2012.04886.x
|View full text |Cite
|
Sign up to set email alerts
|

Low‐dose aspirin for in vitro fertilization or intracytoplasmic sperm injection: a systematic review and a meta‐analysis of the literature

Abstract: vitro fertilization or intracytoplasmic sperm injection: a systematic review and a meta-analysis of the literature. J Thromb Haemost 2012; 10: 2075- 85.Summary. Background: It was hypothesized that low-dose aspirin could improve implantation rates in subsequent pregnancies in women undergoing in vitro fertilization (IVF)/ intracytoplasmic sperm injection (ICSI). Previous studies have shown inconclusive results or focused on surrogate endpoints. We therefore conducted a systematic review and meta-analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 53 publications
1
35
0
Order By: Relevance
“…1920 A systematic review with less stringent quality criteria found that although pregnancy rates were increased with LDA (OR 1·19, 95% CI: 1·01, 1·39), live birth rates were not affected (OR 1·08, 95% CI: 0·82, 1·68). 21 Our study is the first and largest to show that LDA does not decrease pregnancy loss when initiated preconception among women with a history of only one to two prior pregnancy losses. Taken together with previous findings, LDA alone has not been shown to reduce rates of pregnancy loss in any population.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…1920 A systematic review with less stringent quality criteria found that although pregnancy rates were increased with LDA (OR 1·19, 95% CI: 1·01, 1·39), live birth rates were not affected (OR 1·08, 95% CI: 0·82, 1·68). 21 Our study is the first and largest to show that LDA does not decrease pregnancy loss when initiated preconception among women with a history of only one to two prior pregnancy losses. Taken together with previous findings, LDA alone has not been shown to reduce rates of pregnancy loss in any population.…”
Section: Discussionmentioning
confidence: 69%
“…These data indicate that LDA may have a favorable effect on fecundity or implantation for a sub-group of women, and is not inconsistent with some IVF studies showing effects on implantation 15 but not live birth rates. 21 …”
Section: Discussionmentioning
confidence: 99%
“…The use of aspirin in the improvement of IVF/ICSI outcomes has been tested in many RCTs and has been reviewed in two recent systematic reviews and meta-analyses, including 17 and 13 trials, respectively. Findings clearly show that aspirin treatment is not efficacious to improve the number of live births [93,94].…”
Section: Intervention In Assisted Reproductive Technologiesmentioning
confidence: 97%
“…Two recent meta-analyses examined this issue. 12,13 Randomized controlled studies comparing aspirin with placebo or no treatment in women undergoing in vitro fertilization or intracytoplasmic sperm injection were eligible for both; however, the inclusion and exclusion criteria, as well as the analysis methods, differed between the 2 systematic reviews. The timing, dose, and duration of aspirin use varied between individual studies.…”
Section: Antithrombotic Therapy To Enhance the Likelihood Of Success mentioning
confidence: 99%
“…Both meta-analyses concluded that there was no good evidence that aspirin improved live birth rate compared with placebo or no treatment. 12,13 Although one systematic review showed a small but statistically significant increase in pregnancy rate in women randomized to low-dose aspirin, this difference was not maintained when high-quality studies alone were analyzed. 13 Therefore, at this time, the routine use of aspirin in patients undergoing assisted reproduction cannot be recommended.…”
Section: Antithrombotic Therapy To Enhance the Likelihood Of Success mentioning
confidence: 99%